Relation of antimullerian hormone with the clinical signs of hyperandrogenism and polycystic ovary morphology. (February 2014) - Sahmay, Sezai; Aydın, Yavuz; Atakul, Nil; Aydogan, Begum; Kaleli, Semih
Abstract The relation of antimullerian hormone (AMH) levels with the clinical and biochemical markers of polycystic ovary syndrome (PCOS) could be different. A total of 463 PCOS patients were evaluated in this cross-sectional study. Groups were constructed according to polycystic ovarian morphology (PCOM) and menstrual cycle-length. The relation of serum AMH with androgenic hormones, menstrual cycle-length and clinical signs of PCOS were investigated. A powerful positive relation was found between the PCOM and AMH levels (odds ratio = 2.49). There was a negative correlation between age and AMH level (p < 0.001, r[correlation coefficent] = −0.155). Positive correlations were found between luteinizing hormone (LH) and AMH (p < 0.001, r = 0.25) and also between cycle length and AMH (p < 0.01, r = 0.27). We found a negative week correlation between AMH and follicle-stimulating hormone (FSH) (p = 0.01, r = −0.19). After controlling main androgenic hormones, AMH was found to be correlated with the Ferriman–Gallway score (p = 0.03, r = 0.18). There was a positive relationship between hirsutism and AMH (odds ratio = 1.43), but no correlation between AMH and other parameters of clinical hyperandrogenism like hair-loss, acne and seborrhea were identified. The strongest relation was presented between the AMH levels and PCOM. Also, cycle-length correlated well with the AMH levels. The relationship between hirsutism and AMH is found to be independent from androgenic hormones.